Religious Identification, Beliefs, and Practices Among Turkish Belgian and Moroccan Belgian Muslims: Intergenerational Continuity and Acculturative Change - Güngör, Derya (Journal of cross-cultural psychology, 2011)
In light of the religious vitality of Muslim immigrants in historically Christian and highly secularized West-European societies, this study addresses three related questions: (a) How does childhood religious transmission affect adult religiosity among second-generation Muslims? (b) How do acculturating groups as proximal acculturation contexts affect effective transmission? and (c) How do second-generation acculturation orientations affect the transmission process? Using the cross-cultural TIES (“The Integration of the European Second Generation”) surveys among adult community samples of Turkish and Moroccan Belgian Muslims in two cities (Ns = 500 and 481), cross-cultural Structural Equation Models were tested in the four groups to estimate the paths from childhood religious transmission to adult religiosity and acculturation orientations as latent dependent variables. As expected, (a) religious transmission was generally effective for religious identification, beliefs, and practices across groups, yet (b) transmission was most effective in the Turkish Belgian groups as acculturation contexts with high collective cultural continuity. And finally (c) across groups and religious dimensions, individual orientations toward heritage culture maintenance strengthened effective transmission, and host culture adoption played a minor role. We conclude that the religious life of the second generation is part of a continued orientation toward the heritage culture in acculturating families and communities.